Increasing Knowledge of Pregnant Mothers About Iud Contraception Methods On The Use Of Kopiku Application - Meti Patimah; Tatu Septiani Nurhikmah; Noorhayati Novayanti; Ratni N; Adila Fitria; Ihat Sholihat; Prilly Indah Gunawan; Sri Ayu Jaoza (LPPM Universitas Muhammadiyah Tasikmalaya, 2022)
Problems related to the stagnation of the family planning program in Indonesia are thought to be caused by the level of contraceptive use and unmet need for family planning, a decrease in fertility or fertility rates, an increase in the proportion of early marriage, limited knowledge of reproductive health, and sexual activity outside of marriage which leads to Total Maternal Mortality Rate (MMR). The purpose of this activity is to implement the ¨KOPIKu¨ application. This community partnership service is carried out in Cilamajang Village. Kawalu District, Tasikmalaya City, which is the working area of ??the Karanganyar Community Health Center for 35 primigravida III trimester pregnant women. This activity is an application of the ¨KOPIKu¨ My Choice of Contraception which is installed on a smartphone. The results show that the knowledge of mothers before using the KOPIKu application was mostly in the less category at 85.7%, while the mother's knowledge after using the ¨KOPIKu aplikasi application was mostly in the good category at 82.9%.